2008
DOI: 10.1080/13658810701348971
|View full text |Cite
|
Sign up to set email alerts
|

Grassroots groups as stakeholders in spatial data infrastructures: challenges and opportunities for local data development and sharing

Abstract: This paper investigates the unique challenges of an expanding group of stakeholders making demands upon shared geospatial data resources: non governmental organisations participating in local governance. In spite of efforts to improve local data integration in spatial data infrastructures and development of strategies from public participation GIS to expand access to geospatial data and technologies, grassroots data users still experience difficulties with the accessibility, quality, and usefulness of local go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 42 publications
0
78
0
1
Order By: Relevance
“…Without appropriate metadata, questions around database structures, quality and provenance arise for re-users (Elwood, 2008;Sayogo & Pardo, 2013), and datasets are unusable by third parties without significant direct communication between research teams about how the dataset was constructed (Volk et al, 2014). It has been widely observed that a lack of quality metadata is a significant barrier to data sharing and re-use in various disciplines, making effective data re-use impossible in most cases (Alter & Vardigan, 2015;Volk et al, 2014;Reichman et al, 2011).…”
Section: Data Sharing Infrastructure and Managementmentioning
confidence: 99%
“…Without appropriate metadata, questions around database structures, quality and provenance arise for re-users (Elwood, 2008;Sayogo & Pardo, 2013), and datasets are unusable by third parties without significant direct communication between research teams about how the dataset was constructed (Volk et al, 2014). It has been widely observed that a lack of quality metadata is a significant barrier to data sharing and re-use in various disciplines, making effective data re-use impossible in most cases (Alter & Vardigan, 2015;Volk et al, 2014;Reichman et al, 2011).…”
Section: Data Sharing Infrastructure and Managementmentioning
confidence: 99%
“…This includes the comparison of activism across global and local scales (Kurtz, 2003;Martin, 2007), neighborhood or community-based organizing (Elwood, 2008(Elwood, , 2006Martin, 2007), institutional hierarchies (Leitner et al, 2008;Martin et al, 2003) and place-framing, the legitimization of an agenda by constituting place identity through communicative framing (Martin, 2003). Occupy drew inspiration from international resistances that formed in the place of the public squares of Tehran and Spain.…”
Section: Contentious Politics and The Geographic Extensionmentioning
confidence: 99%
“…Research on SDIs and other spatial data sharing structures has not specifically considered the challenges facing grassroots data users. This is addressed by Elwood [3] who emphasizes the need for local data integration and accessibility to local users. SDIs are predicated on an assumption of openness to data sharing and exchange, conceptualizing data as a public good and assuming institutional and individual openness to sharing.…”
Section: Overview Of Related Literaturementioning
confidence: 99%